What about Bob? - Oz, Frank; Ziskin, Laura; Williams, Bernard; Schulman, Tom.; Murray, Bill, 1950-; Dreyfuss, Richard; Hagerty, Julie; Korsmo, Charlie, 1978-; Erbe, Kathryn; Sargent, Alvin; Touchstone Pictures; Touchwood Pacific Partners I.; et al. ([Burbank, Calif.] : Touchstone Home Video : distributed by Buena Vista Home Entertainment, 2000)
Bob Wiley, a troubled but lovable therapy patient, seeks help from noted psychiatrist Dr. Leo Marvin. When the doctor leaves town to go on a quiet family vacation, Bob, afraid of being alone, follows--showing up unexpectedly at the therapist's lakeside retreat. Bob becomes the houseguest that just won't leave.
Originally released as a motion picture in 1991.
Special features include: theatrical trailer.
Music, Miles Goodman ; editor, Anne V. Coates ; director of photography, Michael Ballhaus.
Bill Murray, Richard Dreyfuss, Julie Hagerty, Charlie Korsmo, Kathyrn Erbe.
MPAA rating: PG.
DVD, 2.0 Dolby surround, widescreen presentation (aspect ratio: 1.85:1).
Keywords: Psychotherapy patients -- Drama; Psychiatrists -- Drama; Comedy films; Feature films; Video recordings for hard of hearing people